2018
DOI: 10.3168/jds.2017-14139
|View full text |Cite
|
Sign up to set email alerts
|

Potential probiotic characterization of Lactobacillus reuteri from traditional Chinese highland barley wine and application for room-temperature-storage drinkable yogurt

Abstract: The aim of this study was to select probiotic strains that could be used in drinkable yogurt to yield viable cells following storage at room temperature (RT). The uniquely high altitude conditions in Tibet and the alcoholic environment of certain products, such as the highland barley wine homemade in Tibet, may induce unusual characteristics of microbial strains. A total of 27 lactic acid bacteria were isolated from homemade highland barley wines. One strain, Lactobacillus reuteri WHH1689, demonstrated no abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Probiotics are non‐pathogenic live microorganisms, which confer health benefits to the host when consumed in adequate amount. Generally, probiotics provide health benefits when their number exceeds the value of Log 6 CFU per ml or g of food (Chen et al, ). Consumption of probiotics stimulates the growth of beneficial microorganisms and inhibition of pathogens, which in turn improve intestinal balance, and reduces the risk of gastrointestinal (GI) diseases in host, alleviate lactose intolerance, high cholesterol level, diarrhea, constipation, inflammatory bowel disease, and food allergies (Angmo, Kumari, & Bhalla, ).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are non‐pathogenic live microorganisms, which confer health benefits to the host when consumed in adequate amount. Generally, probiotics provide health benefits when their number exceeds the value of Log 6 CFU per ml or g of food (Chen et al, ). Consumption of probiotics stimulates the growth of beneficial microorganisms and inhibition of pathogens, which in turn improve intestinal balance, and reduces the risk of gastrointestinal (GI) diseases in host, alleviate lactose intolerance, high cholesterol level, diarrhea, constipation, inflammatory bowel disease, and food allergies (Angmo, Kumari, & Bhalla, ).…”
Section: Introductionmentioning
confidence: 99%
“…L. reuteri has been affiliated to different hosts, which might be exposed to different levels and types of antimicrobials and is commercially used as probiotic in food and feed [11,12,58,59]. The results of this study indicated that L. reuteri poultry isolates harbour some AMR genes.…”
Section: Reuterin Synthesismentioning
confidence: 75%
“…The whole genome sequence of L. reuteri WHH1689 have been previously reported and deposited at Gen Bank with accession number CP027805 (Chen, Chen, Chen, Ren, Ge, Kang, et al., ). The genomic sequences of other four L. reuteri strains are available from NCBI data base (http://www.ncbi.nlm.nih.gov/): L. reuteri DSM 20016 (NC_009513.1) L. reuteri TD1 (NC_021872.1), L. reuteri SD2112 (:NC_015697.1), L. reuteri I5007 (:NC_021494.1).…”
Section: Methodsmentioning
confidence: 99%
“…Comparative genomic analysis could reveal evolutionary process and genetic properties of various species based on genome map and sequences. The whole genome sequences of L. reuteri WHH1689 has been completed in our lab (Chen, Chen, Chen, Ren, Ge, Li, et al., ; Chen, Chen, Chen, Ren, Ge, Kang, et al., ). L. reuteri strains such as DSM20016 (Susan, Iyappan, Vijaya, & Rajnish, ), JCM 1112 (Morita et al., ), SD2112 (Báth, Roos, Wall, & Jonsson, ), I5007 (Hou et al., ), TD1 (Leonard et al., ) could be used to annotate the genome for further research.…”
Section: Introductionmentioning
confidence: 99%